Subjective and Objective Appraisal of Activity in Adults with Obstructive Sleep Apnea - Eileen R. Chasens; Susan M. Sereika; Martin P. Houze; Patrick J. Strollo (Journal of Aging Research)
Objective. This study examined the association between obstructive sleep apnea (OSA), daytime sleepiness, functional activity, and objective physical activity. Setting. Subjects (N=37) being evaluated for OSA were recruited from a sleep clinic. Participants. The sample was balanced by gender (53% male), middle-aged, primarily White, and overweight or obese with a mean BMI of 33.98 (SD=7.35; median BMI=32.30). Over 40% reported subjective sleepiness (Epworth Sleepiness Scale (ESS) ≥10) and had OSA (78% with apnea + hypopnea index (AHI) ≥5/hr). Measurements. Evaluation included questionnaires to evaluate subjective sleepiness (Epworth Sleepiness Scale (ESS)) and functional outcomes (Functional Outcomes of Sleep Questionnaire (FOSQ)), an activity monitor, and an overnight sleep study to determine OSA severity. Results. Increased subjective sleepiness was significantly associated with lower scores on the FOSQ but not with average number of steps walked per day. A multiple regression analysis showed that higher AHI values were significantly associated with lower average number of steps walked per day after controlling patient's age, sex, and ESS. Conclusion. Subjective sleepiness was associated with perceived difficulty in activity but not with objectively measured activity. However, OSA severity was associated with decreased objective physical activity in aging adults.